Fundamentals of shareholder tax capitalization - Guenther, David A.; Sansing, Richard (Journal of Accounting and Economics, 2006)
We investigate how shareholder-level taxes are capitalized into stock prices using a model that incorporates the investment and payout decisions of a firm and the investment alternatives available to investors. Shareholder taxes affect stock prices both indirectly, via the effect of taxes on corporate investment decisions, and directly, by reducing both the mean and variance of after-tax returns. In our model, tax capitalization is not eliminated by the presence of tax-exempt investors, does not depend on whether equity is composed of contributed capital or retained earnings, and does not depend on the tax rate faced by a hypothetical marginal investor.